PERGESARAN PENEGAKAN HUKUM YANG POSITIVISTIK MENUJU KE PENEGAKAN HUKUM YANG PROGRESIF - Faishal Taufiqurrahman; Efendi Ibnususilo; Monika Melina (JOURNAL EQUITABLE, 2023)
Law enforcement occurred in Indonesia does not reflect the values ​​of justice expected by the public, so was born the concept of progressive law to resolve the problem. This study examines: First, the cause of law enforcement in Indonesia does not reflect the values ​​of justice; second, the role of the concept of progressive law enforcement in solving the problems that occurred in Indonesia. The results of this study concluded: First, the cause of law enforcement did not indicate the value of justice is: (i) law enforcement officers who put forward the procedural aspects, (ii) the existence of discrimination by law enforcement and (iii) the law as can be bought. Second, the role of the concept of progressive law in law enforcement in Indonesia is a progressive law concept is not just enforce the rule of law itself, but the law must be enforced are the values ​​of justice contained in the sound of formal rules and the values ​​of justice in society.